Perancangan Vaksin 3H5S HVC Sederhana Secara In Silico: Simple In Silico 3H5S Vaccine Design - Jumiati; Toepak, Erwin Prasetya (Jurnal Jejaring Matematika dan Sains, 2021)
In silico test is a term used for experiments or tests carried out using computer simulation methods. HCV is a flavivirus. The hepatitis C genome is a 9.6 kb single-stranded RNA molecule that serves as a template for translation and replication. In this study, the HVC 3H5S protein sequence was searched with NCBI and B cell epitope prediction using the BepiPred method. After all the steps have been carried out, the results of the observations are obtained. The first is in the HVC 3H5S protein sequence search stage, the threshold value and overall prediction for the Protecting Antigen are obtained, the threshold value is 0.4 and the overall prediction for the Protecting Antigen is 0.4816 (probable antigen). And based on the prediction results of B cell epitopes, data related to the sequence name, initial position, final position, and score of the epitope were obtained. The protein sequence obtained from the data consists of a sequence of letters, each letter is the code of an amino acid. All protein sequences are made in FASTA format to make it easier to use in software or servers. The prediction results of B cell epitopes using the BepiPred server produce several epitope sequences that are equipped with their binding specificity scores. The predicted results of the B cell epitopes obtained display the positions of the epitopes that describe the level of recognition of the B cell epitopes or binding with antibodies so that in determining the vaccine sequence later, the predicted epitopes are selected based on their level of accessibility.